2005
DOI: 10.1111/j.1440-1746.2004.03572.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of genotype B and C hepatitis B virus‐induced chronic hepatitis in relation to the basic core promoter and precore mutations

Abstract: Genotype B patients were older, had earlier HBeAg seroconversion and exhibited more severe lobular necroinflammation, less portal inflammation and fibrosis than genotype C patients. This genotypic difference is related to the basic core promoter and precore mutations irrespective of 1858C. (c) 2004 Blackwell Publishing Asia Pty Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…These studies included between 90 and 4,841 patients followed up for up to 14 years [33,[38][39][40][41][42]. They confirmed that HBeAg seroconversion occurred at a significantly younger age for those infected with genotype B than genotype C [15,38,40,42] and that increased risk of fibrosis was associated with genotype C [39,40].…”
Section: Hbv Genotype Csupporting
confidence: 53%
See 2 more Smart Citations
“…These studies included between 90 and 4,841 patients followed up for up to 14 years [33,[38][39][40][41][42]. They confirmed that HBeAg seroconversion occurred at a significantly younger age for those infected with genotype B than genotype C [15,38,40,42] and that increased risk of fibrosis was associated with genotype C [39,40].…”
Section: Hbv Genotype Csupporting
confidence: 53%
“…Ideally, these investigations should be population-based studies that compare persons with different genotypes, conducted prospectively over a long period of time to precisely identify the risk of sequelae associated with each genotype and subgenotype, such as have been done in Asia and Alaska [15,21,33,[38][39][40][41][42]. At this time, several HBV genotypes and subgenotypes, such as genotypes A1 and D, that have been associated with increased risk of cirrhosis and HCC in cross-sectional studies have not been evaluated in prospective longitudinal studies.…”
Section: Recombinant Hbv Genotypes and Coinfection With More Than Onementioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes of HBV show a distinct geographic distribution 10,11 and are associated with different clinical outcomes, responses to treatment with interferon or nucleotide analogues, and rates of fulminant hepatitis. [12][13][14][15][16][17][18][19][20][21] Historically, 96.9% of HBV isolates from Japanese individuals with chronic hepatitis B belong to genotypes B or C 14 ; however, since 2000, HBV/A has spread in urban areas through homosexual intercourse. 18,[21][22][23] The positivity rate for HBV infection in Japanese HIV-1-infected individuals is 8.9%, and half of HBV-infected individuals harbor the genotype A virus.…”
mentioning
confidence: 99%
“…HBV is classified into 8 genotypes (A-H), each showing a distinct geographical distribution and disease progression. HBV genotype C is believed to be associated with a higher risk of reactivation and progression to cirrhosis compared to HBV genotype B [22,23] . Whether hepatitis B virus (HBV) genotypes influence the response to antiviral treatment remains controversial.…”
Section: Discussionmentioning
confidence: 99%